Assessing production constraints, management and use of sorghum diversity in north-east Ghana: A diagnostic study - Kudadjie, C.Y.; Struik, P.C.; Richards, P.; Offel, S.K. (NJAS - Wageningen Journal of Life Sciences, 2004)
This paper reports on the results of a diagnostic study conducted to assess the problems and needs of sorghum farmers in north-east Ghana with the aim of determining the type of research that would be useful for them in their own context. The importance of the crop and its position within the cropping system are identified. Sorghum is still an integral part of the livelihoods of farmers. The crop is very versatile and not only contributes to food security but also plays a part in the socio-culrural, socio-economic, and religious aspects of the lives of farmers. Farmers have different uses for the varieties they grow, which depends on the morphological, agronomic and gastronomic traits of the crop. Sorghum varieties introduced from the research institutions have several problems including lodging, poor grain quality, bird damage and precocious germination. Farmers have developed management strategies for dealing with some of these problems. Nevertheless, further work is required by breeders to make the varieties more acceptable to users. Sorghum production constraints identified include poor soils, erratic rainfall and pest infestation of the grain during storage. The diagnostic study suggests that because farmers produce their own seed, enhancing their ability to improve the quality of their seed would be of benefit to them. The study further underscores the importance and value of diversity for farmers. It also highlights their understanding of diversity, and management and use of variation in their agronomic practices. Areas identified for further research together with farmers aim at enhancing farmers' knowledge towards strengthening their practices in diversity management and improving seed storage practices.
Keywords: Biodiversity; Farmers' knowledge; Maize; Seed management; Sorghum bicolor; Variety